The immersed discontinuous semi-discrete finite element method: A comparison of surface-immersed stiffened and body-immersed stiffened sandwich plate. (1st December 2018) - Li, Tianyu; Kang, Hua
Highlight: A discontinuous immersed finite element method is developed to study the stiffened laminated plate structures. Two types of stiffened plates are studied and compared in the aspect of strength and stability. The body-immersed stiffened plate has a better strength and stability than the surface-immersed case. Numerical results are verified by the solid finite element software ANSYS. Abstract: Two types of stiffened sandwich plate structures are analyzed and compared. The first is surface-immersed stiffened sandwich plate, in which the stiffener's top surface is bonded to the bottom surface of the sandwich plate. The second is body-immersed stiffened sandwich plate, in which the stiffener is immersed into the 3-D space of core soft layer. The immersed discontinuous semi-discrete finite element method is developed and applied to study the stiffened plates. The results are compared with ANSYS to verify the accuracy of the method. The convergence study is also given: an exponential convergence is observed. The stiffening efficiency is compared between the two types of stiffened sandwich plates. It is observed that the body-immersed stiffened plate has better strength and stability. The motivation to develop this method is to use a much smaller number of degree-of-freedom to analyze those stiffened plates, for which traditional finite element methods may not be convenient because of the difficulty in the generation of high-quality compatible mesh.